Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1186/1748-717x-7-82
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase II trial of urethral sparing intensity modulated radiation therapy in low-risk prostate cancer: implications for focal therapy

Abstract: BackgroundLow-risk prostate cancer (PCa) patients have excellent outcomes, with treatment modality often selected by perceived effects on quality of life. Acute urinary symptoms are common during external beam radiotherapy (EBRT), while chronic symptoms have been linked to urethral dose. Since most low-risk PCa occurs in the peripheral zone (PZ), we hypothesized that EBRT using urethral sparing intensity modulated radiation therapy (US-IMRT) could improve urinary health-related quality of life (HRQOL) while ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…The date of treatment was also slightly different, such that IMRT and brachytherapy technique and outcomes had improved by the time the SBRT cohort was collected [25][26][27]. However, we note that IMRT was associated with an MCD only for bowel QOL in our multivariable model, and margin reduction through IGRT has been shown to minimize bowel QOL impact in other studies using the EPIC survey [26,27]. Therefore, modern IMRT is likely to cause few QOL MCDs at 2 years, as we found for SBRT.…”
Section: Discussionmentioning
confidence: 99%
“…The date of treatment was also slightly different, such that IMRT and brachytherapy technique and outcomes had improved by the time the SBRT cohort was collected [25][26][27]. However, we note that IMRT was associated with an MCD only for bowel QOL in our multivariable model, and margin reduction through IGRT has been shown to minimize bowel QOL impact in other studies using the EPIC survey [26,27]. Therefore, modern IMRT is likely to cause few QOL MCDs at 2 years, as we found for SBRT.…”
Section: Discussionmentioning
confidence: 99%
“…Another study was a randomized Phase II trial using an intensity-modulated radiation therapy (IMRT) urethral sparing technique (42). Patients in the urethral sparing arm had a mean reduced dose of 36.2% and 9.6% to the proximal and distal urethra compared with standard IMRT plans.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have decreased the bladder neck dose by reducing the anterior/ superior PTV expansion to 3 mm. From our clinical experience, such modifications have reduced the incidence and severity of the late urinary symptom flare and patient reported dysuria without increasing the risk of biochemical failures (27).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment DVH goals included a maximum dose of 37 Gy to <5 cc of the bladder and <50% of the membranous urethra. While the prostatic urethra dose was not limited, we found that, by restricting the prescription isodose line to ≥75%, we were able to reduce the prostatic urethra dose to 133% of the prescription dose (27,28). Target position was verified every 30-60 s during each treatment using paired, orthogonal x-ray images (29).…”
Section: Sbrt Treatment Planning and Deliverymentioning
confidence: 99%